Modulation of cardiac cytochrome P450 in patients with heart failure. (March 2014) - Aspromonte, Nadia; Monitillo, Francesco; Puzzovivo, Agata; Valle, Roberto; Caldarola, Pasquale; Iacoviello, Massimo
<x xml:space="preserve">Abstract</x> Introduction: There is increasing evidence that cytochrome P450 (CYP) plays a role in the onset, progression and prognosis of cardiovascular disease (CVD), in particular, heart failure (HF). The importance of CYP enzymes in cardiovascular physiology derives from their ability to metabolize arachidonic acid to epoxyeicosatrienoic and hydroxyeicosatetraenoic acids, which are involved in the maintenance of cardiovascular health, including the regulation of vascular tone, cardiac ion channels and heart contractility. Moreover, CYP plays a central role in the Phase I metabolism of drugs and other xenobiotics. Inter-individual variability in expression and function of CYP enzymes is a major factor accounting for individual susceptibility to drug response. Areas covered: This review focuses on current knowledge of the role of CYP enzymes and their metabolites in the pathogenesis of CVD, in particular, HF. The role of CYP enzymes in affecting individual response to cardiovascular drugs is also discussed. The literature search was performed using the PubMed database. Expert opinion: More research is needed to elucidate the mechanisms by which CYP affects the pathophysiology of HF and also the mechanism by which HF alters cardiac and hepatic CYP enzymes.